EFEKTIVITAS TEKNIK BEHAVIOR CONTRACT DALAM MEREDUKSI TOXIC LANGUANGE PADA SISWA SMK AR-RIFAIYAH (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of the behavior contract technique as an effort to reduce toxic language in Ar-Rifayah Vocational High School students. This study uses a quantitative experimental approach with the T-test (paired sample T-test) method. Data collection techniques used are questionnaires, observation and documentation. The data analysis technique of this study uses descriptive analysis and inferential analysis of the T-test (paired sample T-test) to test the research hypothesis. The results showed that there were 12 Ar-Rifayah Vocational High School students who became the research sample. Based on the results of the analysis conducted by the researcher, the significance value of the T-test (paired sample T-test) the researcher obtained a significance value (2-tailed) of 0.000 <0.5, so in this study the researcher concluded that Ha was accepted and Ho was rejected, because the behavior contract technique was proven effective in reducing students' toxic language and there was a significant difference in the level of toxic language of students before and after being given treatment in the form of group counseling services using the behavior contract technique at Ar-Rifayah Vocational High School.